Knowledge and practices of vaccination for children with rheumatic diseases: A single-center study in China - Xiwen Luo; Jing Tao; Min Pang; Zhiyong Zhang; Xuemei Tang (Taylor & Francis Group, 2023)
Patients with pediatric rheumatic diseases (PRDs) have higher morbidity and mortality associated with infectious diseases. Vaccination is an effective way to prevent infection. This study aimed to understand the vaccination status, vaccination-related attitudes, and adverse reactions in patients with PRDs in one of the largest Pediatric Rheumatic and Immune centers in China. A cross-sectional study using an online questionnaire was conducted among the caregivers of patients with PRDs admitted to the Children's Hospital of Chongqing Medical University. 189 valid questionnaires were collected. The most two common PRDs in this study were juvenile idiopathic arthritis (29.6%) and systemic lupus erythematosus (19.6%). Univariate analysis and multivariate logistic regression were used to identify potential factors associated with vaccination completion among these patients. Univariate analysis suggested that the age of onset, course of the disease, treatment duration, disease duration <1 month, disease duration ≥24 months, treatment duration <1 month, use of biological agents, at least one hospitalization, whether with one-time intravenous human immunoglobulin, caregiver concerns about vaccination before or after illness, and vaccine hesitancy may affect the scheduled vaccination completion by age in patients (p < .05). Multivariate logistic regression analysis showed that the age of onset (OR, 1.013; 95% CI, 1.005-1.022; p = .002) and caregiver concerns about vaccination before illness (OR, 0.600; 95% CI, 0.428-0.840; p = .003) independently influenced patients' completion of scheduled vaccinations. This study suggests that rheumatic disease and treatment may influence age-appropriate vaccination. Appropriate education for patients and carers may improve vaccination cognition and attitudes.